2020
DOI: 10.1002/pbc.28300
|View full text |Cite
|
Sign up to set email alerts
|

Hurthle cell carcinoma in childhood: A retrospective analysis of five cases and review of pediatric literature

Abstract: Background the available studies on Hurthle cell carcinoma (HCC) in pediatric age are scarce and based on isolated case reports. Aims of the present study were to review the available pediatric literature on HCC (2000‐2019), to describe the cohort of children with this cancer histotype, and to estimate its relative prevalence in pediatric age. Procedure We retrospectively reconstructed an HCC course in five patients < 19 years who were identified in our departments during the period 2000‐2019, and we reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The new WHO classification distinguishes benign and malignant HCTs on the basis of capsular and vascular invasion ( Figure 4 B), similarly to FTCs [ 73 ]. Although believed to have a poorer prognosis compared to FTCs, it was demonstrated that Hürthle cell cancer has not higher rates of recurrence and does not concentrate less radioiodine [ 74 , 75 , 76 ]. Nevertheless, it has been reported that somatic genomic alterations in malignant HCTs are represented by Mucosal Vascular Address in Cell Adhesion Molecule 1 (MADCAM-1) (20%), EIF1AX (11%), DAXX, PT53 (7%) and Neurofibromatosis type 1 (NF1) (7%) mutations, while no BRAF mutations and a lower rate of NRAS (9%) mutation are encountered in comparison to FTC cases [ 77 , 78 , 79 ] ( Table 2 ).…”
Section: Phenotypic and Molecular Heterogeneity In Ftcmentioning
confidence: 99%
“…The new WHO classification distinguishes benign and malignant HCTs on the basis of capsular and vascular invasion ( Figure 4 B), similarly to FTCs [ 73 ]. Although believed to have a poorer prognosis compared to FTCs, it was demonstrated that Hürthle cell cancer has not higher rates of recurrence and does not concentrate less radioiodine [ 74 , 75 , 76 ]. Nevertheless, it has been reported that somatic genomic alterations in malignant HCTs are represented by Mucosal Vascular Address in Cell Adhesion Molecule 1 (MADCAM-1) (20%), EIF1AX (11%), DAXX, PT53 (7%) and Neurofibromatosis type 1 (NF1) (7%) mutations, while no BRAF mutations and a lower rate of NRAS (9%) mutation are encountered in comparison to FTC cases [ 77 , 78 , 79 ] ( Table 2 ).…”
Section: Phenotypic and Molecular Heterogeneity In Ftcmentioning
confidence: 99%